2021
DOI: 10.3390/v13060952
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins at the Host-Pathogen Interface Targeting Viral Regulatory Elements

Abstract: Viral RNAs contain the information needed to synthesize their own proteins, to replicate, and to spread to susceptible cells. However, due to their reduced coding capacity RNA viruses rely on host cells to complete their multiplication cycle. This is largely achieved by the concerted action of regulatory structural elements on viral RNAs and a subset of host proteins, whose dedicated function across all stages of the infection steps is critical to complete the viral cycle. Importantly, not only the RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 164 publications
(186 reference statements)
0
24
0
Order By: Relevance
“…Viruses recruit host factors for viral replication and several dsRNA binding proteins have been shown to interact with the 3’UTR of flaviviruses [62, 63]. Despite its role as a regulator of RNAi pathways central to antiviral immunity, our work establishes that the RNA binding protein Loqs is hijacked through protein-protein and protein-RNA interactions to promote flavivirus replication in mosquitoes.…”
Section: Discussionmentioning
confidence: 87%
“…Viruses recruit host factors for viral replication and several dsRNA binding proteins have been shown to interact with the 3’UTR of flaviviruses [62, 63]. Despite its role as a regulator of RNAi pathways central to antiviral immunity, our work establishes that the RNA binding protein Loqs is hijacked through protein-protein and protein-RNA interactions to promote flavivirus replication in mosquitoes.…”
Section: Discussionmentioning
confidence: 87%
“…These strategies are in part facilitated by the delocalization of RBPs to the cytoplasm in infected cells, an event that increases the pool of functionally active factors for viral RNA translation. Soon after the discovery of picornavirus IRES elements in 1988 [5,6], it was found that full IRES activity required the action of host factors, as exemplified by the polypyrimidine tract‐binding protein (PTB), poly(rC)‐binding protein 2 (PCBP2), ErbB3‐binding protein 1 (Ebp1, also known as ITAF 45 and PA2G4), or the cold‐shock domain containing E1 (CSDE1, also known as Unr), among others [50–54], reviewed in [38,55].…”
Section: Host Factors Involved In Picornavirus Rna Translationmentioning
confidence: 99%
“…There are various examples of RBPs interacting with picornavirus IRES elements, which are proteolyzed during infection, remodeling their activity on translation after cleavage. Among others, known examples include the PTB protein, the far‐upstream element binding protein 2 (FUBP2), FUBP1, the heterogeneous nuclear ribonucleoprotein (hnRNPK), PCBP2, the Ras GTPase SH3 domain binding protein 1 (G3BP1), and Gemin5 (reviewed in [55]). In the case of PTB, the PV 3C protease recognizes the three isoforms of this protein, generating truncated polypeptides that repress PV IRES activity [59].…”
Section: Regulation Of Picornavirus Translation By Host Factor Proteo...mentioning
confidence: 99%
“…Thus, viral IRESs behave as a complex RNA scaffold interacting with specific RBPs, the 40S ribosomal subunit, or with components of the canonical translational apparatus enabling translation initiation [167,168]. For example, the EMCV IRES directly interacts with eIF4G, an interaction enhanced by eIF4A [169,170].…”
Section: Ires-dependent Translation Initiationmentioning
confidence: 99%